Technologies for the treatment and recovery of nutrients from industrial wastewater - Val del Rio, Angeles, 1980-; Gomez, Jose Luis Campos, 1971-; Corral, Anuska Mosquera, 1969- (Advances in environmental engineering and green technologies (AEEGT) book series., 2017)
"This book investigates emergent research and best practices within the field of wastewater management, highlighting novel technological tools in wastewater treatment, effective nutrient removal technologies, and innovative solutions to quality water preservation practices"--Provided by publisher.